2014
DOI: 10.1103/physreva.90.023816
|View full text |Cite
|
Sign up to set email alerts
|

Scalable numerical approach for the steady-stateab initiolaser theory

Abstract: We present an efficient and flexible method for solving the non-linear lasing equations of the steady-state ab initio laser theory. Our strategy is to solve the underlying system of partial differential equations directly, without the need of setting up a parametrized basis of constant flux states. We validate this approach in one-dimensional as well as in cylindrical systems, and demonstrate its scalability to full-vector three-dimensional calculations in photonic-crystal slabs. Our method paves the way for e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 66 publications
(109 reference statements)
2
101
0
Order By: Relevance
“…Due to their time-dependent nature these equations are, however, usually difficult to solve for all but the most simple cases. In recent years, a much more efficient approach named steady state ab initio lasing theory (SALT) has emerged, which can be used to describe the steady-state lasing of lasers [17][18][19][20][21][22][23]. Among other advances, this new framework has shed light on weakly-scattering random lasers [24], on pump-induced exceptional points [11,12,25,26] and on coherent perfect absorption [27,28] and has opened up new ways of controlling the emission patterns of random as well as of microcavity lasers [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their time-dependent nature these equations are, however, usually difficult to solve for all but the most simple cases. In recent years, a much more efficient approach named steady state ab initio lasing theory (SALT) has emerged, which can be used to describe the steady-state lasing of lasers [17][18][19][20][21][22][23]. Among other advances, this new framework has shed light on weakly-scattering random lasers [24], on pump-induced exceptional points [11,12,25,26] and on coherent perfect absorption [27,28] and has opened up new ways of controlling the emission patterns of random as well as of microcavity lasers [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…4(c). To determine the net-polarization of modes from the 3D simulations on a quantitative level, we expect that taking into account non-linear interactions between the laser modes [26] as well as effects, which are specific to the employed quantum cascade structures [27] will be necessary. An incoherent far-field superposition of 20 modes with the highest PNet is depicted in Fig.…”
mentioning
confidence: 99%
“…Our perturbative solution near threshold confirms an ansatz in the earlier degenerate SALT work [7], in which the circulating and standing-wave solutions were guessed as starting points for a SALT solver and it was conjectured that the resulting four solutions were the only possibilities. Furthermore, we have presented an efficient numerical scheme to track these solutions far above threshold via numerical SALT solvers [14] combined with a simple technique to correct for numerical symmetry breaking. And finally, we have shown that the degeneracy of the C n group Sec.…”
Section: Discussionmentioning
confidence: 99%
“…As explained in Ref. [14], the process for solving for lasing modes begins with the linear problem for the passive poles. Because both the real and imaginary parts of the passive poles are split by the discretization error, the modes will lase at different pump strengths, and even after both modes lase we cannot construct a linear combination of them because the two modes satisfy equations with different real eigenfrequencies.…”
Section: C Nv Symmetry Broken By Discretizationmentioning
confidence: 99%
See 1 more Smart Citation